Extracorporeal Shock Wave Therapy (ESWT) as Part of the Treatment of Delayed Healing of Bone Fracture - Vetterling, Patrick; Bätje, Frank; Schmidt, Jörg (Zeitschrift für Orthopädie und Unfallchirurgie, 2025)
The following paper provides an overview of the procedure of extracorporeal shockwave therapy and a classification of the current literature. The PubMed, Lvivo and WebOfScience databases were searched for “Extracorporeal Shockwave Therapy” and “Fracture nonunion”. A total of 45 studies were identified, 12 of which were included in the analysis after narrowing them down. Fracture healing rates after the application of extracorporeal shockwave therapy (ESWT) averaged 69.25% (52–86%). Overall, it can be seen that the studies are based on small samples (average 154 patients) with a high variance in sample sizes (17–924 patients).
Keywords: extracorporal Shockwave therapy; pseudarthrosis; fracture nonunion